A Mixed‐Extractor Strategy for Efficient Sorting of Semiconducting Single‐Walled Carbon Nanotubes. Issue 8 (27th December 2016) - Liu, Dan; Li, Pan; Yu, Xiaoqing; Gu, Jianting; Han, Jie; Zhang, Shuchen; Li, Hongbo; Jin, Hehua; Qiu, Song; Li, Qingwen; Zhang, Jin
Abstract : A general strategy for sorting semiconducting single‐walled carbon nanotubes (s‐SWNTs) with high efficiency using a mixed‐extractor is reported. When the two extractors have a sufficient difference in binding energy with s‐SWNTs, and skeleton flexibility, the mixture shows enhanced yield for sorting s‐SWNTs. The strategy could be effective when applied to increase the sorting yield of other selective dispersion systems.